MODELING OF THE PROCESSES OF OZONE DISPERSION BY PURIFICATION FACILITY - Татарченко, Галина (SWorldJournal, 2022)
Modeling of the processes of ozone dispersion by a treatment plant in urban areas was carried out. For a single source of ozone emissions, the maximum concentration was calculated to be expected when dangerous wind speeds are expected in the lower atmosp